Influência do cancro basal em Eucalyptus grandis nas propriedades da madeira e polpação kraft - De Souza, Sandra Elizabeth; Sansigolo, Cláudio Angeli [UNESP]; Furtado, Edson Luiz [UNESP]; De Jesus Jr., Waldir Cintra; Oliveira, Rodrigo Rocha (My University, 2010)
The objective of this research is to assess the influences of basal canker on wood properties for the kraft pulp production. The material consisted of seeded E. grandis trees classified into 4 levels of basal canker severity (0, 1, 2 and 3) and installed in three soil types classified by texture (AQ1 and AQ2 - 10 to 15% clay, and LEm2 - 26 to 35 clay). The sampling consisted of randomly selecting five trees for each for each canker severity level and soil type, totaling 60 trees (4 canker levels x 3 soil types x 5 trees). These trees were fallen and cut into sections at 0, 25, 50, 75 and 100% of the commercial height for the collection of disk and logs of wood. The results showed that the soil texture influences in the Eucalyptus canker severity and this fact should be considered when assessing the wood properties and their final destination. The texture of the soil and the severe levels of basal canker influence the wood properties, and therefore the kraft pulping.
Influence of the basal canker on Eucalyptus grandis wood properties and kraft pulping
Keywords: Basic density; Eucalyptus canker; Eucalyptus grandis; Kraft pulping; Wood chemical properties; 4-level; Kraft pulp production; Soil textures; Soil types; Chemical properties; Kraft process; Soils; Textures; Wood; Wood chemicals; Kraft pulp; Chemical Properties; Eucalyptus Grandis; Kraft Pulping; Soil; Texture; Wood Density